Synthesis of Complexes of Co, Ni, Cu and Zn with N,N’-Ethylene-bis(2-phenyl)glycinonitrile Ligand - Golchoubian, Hamid; Razinataj, Ali (Asian Journal of Chemistry, 2010)
The new chelating ligand N,N'-ethylene-bis(2-phenyl)- glycinonitrile and its corresponding complexes with bivalent metals of Co, Ni, Cu and Zn were prepared and characterized by IR, NMR, UV/Vis spectroscopy and elemental analysis.